2015
DOI: 10.5688/ajpe798123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Revised Method for Evaluating Peer-graded Assignments in a Skills-based Course Sequence

Abstract: Objective. To evaluate the modified peer-grading process incorporated into the SOAP (subjective, objective, assessment, plan) note sessions in a skills-based pharmacy course sequence. Design. Students assessed a de-identified peer's SOAP note in a faculty-led peer-grading session followed by an optional grade challenge opportunity. Using paired t tests, final session grades (peergraded with challenge opportunity) were compared with the retrospective faculty-assigned grades. Additionally, students responded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A previous study also demonstrated that students found faculty guidance helpful (93%) in the peer assessment of SOAP notes. 9 Our findings were also congruent with other studies in medical and pharmacy education where anonymity was proven to be helpful for conducting peer assessments. 10,15,16 However, concerns could persist even when the process was anonymous.…”
Section: Subthemes Representative Quotessupporting
confidence: 89%
See 3 more Smart Citations
“…A previous study also demonstrated that students found faculty guidance helpful (93%) in the peer assessment of SOAP notes. 9 Our findings were also congruent with other studies in medical and pharmacy education where anonymity was proven to be helpful for conducting peer assessments. 10,15,16 However, concerns could persist even when the process was anonymous.…”
Section: Subthemes Representative Quotessupporting
confidence: 89%
“…In some studies, peer-assessment grades were higher compared to faculty or self-assigned grades. 13,15 On the other hand, Wu and colleagues 10 found that students had similar confidence level in their own skills relative to that of their peers (95% versus 92%) and Storjohann and colleagues 9 found no significant difference between peer assessment versus faculty-assigned SOAP note scores. We hypothesize that conflicting results might be related to students' familiarity with the content being assessed and the amount of training they received.…”
Section: Subthemes Representative Quotesmentioning
confidence: 99%
See 2 more Smart Citations
“…Australian and United States studies have reported no significant difference between the SOAP notes scores of students vs. faculty members. 3,4 Many academic institutions have incorporated online learning (e-learning) to foster the notion of lifelong learning as well as to provide students with flexibility and convenience to learn when and where they are most comfortable. Technology has also allowed students to look up information independently and instill responsibility for self-directed learning.…”
Section: Introductionmentioning
confidence: 99%